Ritual Penti Pada Masyarakat Desa Ndehes, Kecamatan Wae Ri’i, Kabupaten Manggarai, Flores, Nusa Tenggara Timur - Yansen Agus, Arnoldus; Arjani, Ni Luh; Darmana, I Ketut (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p26, 2018)
Penti is a customary rite, the ancestral heritage of the Ndehes, Manggarai, as a medium of gratitude to God for the crops gained during the year and also known as the New Year celebration for the Ndehes, Manggarai people. Penti is also an attempt to reconcile the relationship between man and his neighbor (relative), man with nature, and man with God. The problem studied is to know how the process of ritual pent in the villagers of Ndehes, Manggarai, Flores, NTT and the functions and meanings contained in the ritual penti for the villagers of Ndehes, Manggarai, Flores, NTT. The purpose of this research is to know the background of ritual pent, pent ritual process, and the function and meaning of ritual penti for the people of Ndehes Village, Manggarai Regency, Flores, NTT. Researchers use qualitative methods, as well as data collection techniques with participant observation techniques, in-depth interviews and literature studies. Informants are determined based on the background and knowledge of the informant so that it can assist in the research process about the pent ritual. The theory of functionality proposed by Branislaw Malinowski became the foundation used for this study coupled with religious concepts from other scholars such as Emile Durkheim and Koentjaraningrat. The pent ritual is able to regulate the customary and religious life of the people of Ndehes. Ritual penti has the function and meaning contained in each series of its show process, both latent function and manifest function, and the meaning - meaning in ritual penti which become basis of social life of Ndehes Village community.